2022
DOI: 10.1101/2022.10.04.22280689
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population-level relative effectiveness of the COVID-19 vaccines and the contribution of naturally acquired immunity

Abstract: Background: Immune protection against SARS-CoV-2 can be induced by natural infection or vaccination or both. The interaction between vaccine-induced immunity and naturally acquired immunity at the population level has been understudied. Methods: We used regression models to evaluate whether the impact of COVID-19 vaccines differed across states with different levels of naturally acquired immunity from March 2021 to April 2022 in the United States. Analysis was conducted for three evaluation periods separately… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…While existing research has predominantly focused on individual factors such as vaccination rates 1,2,3,4,5,6,7 or socioeconomic parameters 7,8,9 , associated with reduced pandemic excess mortality or COVID-19 fatalities, this study takes an approach by simultaneously considering both vaccination rates and a state's economic well-being, measured by its annual GDP per capita. Crucially, a state's GDP per capita serves as an indicator of its economic capacity.…”
Section: Introductionmentioning
confidence: 99%
“…While existing research has predominantly focused on individual factors such as vaccination rates 1,2,3,4,5,6,7 or socioeconomic parameters 7,8,9 , associated with reduced pandemic excess mortality or COVID-19 fatalities, this study takes an approach by simultaneously considering both vaccination rates and a state's economic well-being, measured by its annual GDP per capita. Crucially, a state's GDP per capita serves as an indicator of its economic capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found a negative correlation between vaccination rates and excess mortality associated with COVID-19 ( 20 24 ). In theory, the mere fact that such a correlation exists cannot be proof of a causal relationship.…”
Section: Introductionmentioning
confidence: 99%